Immunogenicity and safety following primary and booster vaccination with a hexavalent diphtheria, tetanus, acellular pertussis, hepatitis B, inactivated poliovirus and Haemophilus influenzae type b vaccine: a randomized trial in the United States. Issue 4 (3rd April 2019) - Klein, Nicola P.; Abu-Elyazeed, Remon; Cheuvart, Brigitte; Janssens, Winnie; Mesaros, Narcisa
ABSTRACT: Combined hexavalent diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliomyelitis and Haemophilus influenzae type b vaccine (DTaP-HBV-IPV/Hib) can further reduce the number of injections in pediatric immunization schedules of countries currently using pentavalent DTaP combination vaccines. This open-label, randomized, multicenter study (NCT02096263) conducted in the United States evaluated the immunogenicity and safety of DTaP-HBV-IPV/Hib vaccine compared with concomitant administration of DTaP-HBV-IPV and HibA or DTaP-IPV/Hib and HBV vaccines. We randomized (1:1:1) infants to receive 3-dose priming with DTaP-HBV-IPV/Hib boosted with DTaP+ HibB, DTaP-HBV-IPV+ HibA boosted with DTaP+ HibA, or DTaP-IPV/Hib+ HBV boosted with DTaP-IPV/Hib, at 2, 4, 6, and 15–18 months of age. We enrolled and vaccinated 585 participants, 486 received a booster, and 476 completed the study. Of these, 466 participants were included in the primary and 408 in the booster according-to-protocol cohorts for immunogenicity. We demonstrated non-inferiority of DTaP-HBV-IPV/Hib vaccine to DTaP-HBV-IPV+ HibA co-administered vaccines in terms of geometric mean concentrations for pertussis antibodies post-primary vaccination. Post-primary vaccination, seroprotection/seropositivity rates for all vaccine antigens were similarly high between DTaP-HBV-IPV/Hib (≥ 94.8%), DTaP-HBV-IPV+ HibA (≥ 98.1%) or DTaP-IPV/Hib+ HBV (≥ 97.8%) groups. We observed robust immune responses post-booster, indicating effective priming by the 3 regimens. Reactogenicity was similar in the 3 groups. Twenty-eight serious adverse events were reported during the study; 3 were considered related to vaccination and resolved by the end of the study. These results confirm that DTaP-HBV-IPV/Hib could be a valuable additional source of pediatric DTaP, IPV, HBV, and Hib-containing vaccine in countries that currently use multivalent vaccines.